2020
DOI: 10.1002/cia2.12099
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world use of dupilumab for 53 patients with atopic dermatitis in Japan

Abstract: Dupilumab was effective for 53 patients with moderate‐to‐severe AD in our daily practice. TARC reduction, however, did not necessarily reflect improved AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 6 publications
0
13
1
Order By: Relevance
“…(2021) United Kingdom 30 164 75.31 The most common side effects were eye symptoms, occurring in 43.1% of patients, with 16.3% developing conjunctivitis. Matsutani et al. (2020) Japan 16 53 ND EASI score, DLQI, and POEM decreased by 73.1%, 73.6%, and 72.1%, respectively.…”
Section: Effectiveness and Safety Of Dupilumab For Ad In The Real Worldmentioning
confidence: 94%
See 2 more Smart Citations
“…(2021) United Kingdom 30 164 75.31 The most common side effects were eye symptoms, occurring in 43.1% of patients, with 16.3% developing conjunctivitis. Matsutani et al. (2020) Japan 16 53 ND EASI score, DLQI, and POEM decreased by 73.1%, 73.6%, and 72.1%, respectively.…”
Section: Effectiveness and Safety Of Dupilumab For Ad In The Real Worldmentioning
confidence: 94%
“…Real-world evidence of the effectiveness and safety of dupilumab for atopic dermatitis Accumulating real-world evidence has ensured the effectiveness and tolerable safety of dupilumab both in the short term and in the long term. The articles searched in PubMed and Google Scholar are shown in Table 1 (Ariëns et al, 2020, Ariëns et al, 2021, Faiz et al, 2019, Fargnoli et al, 2020, Fargnoli et al, 2019, Jang et al, 2020, Jo et al, 2020a, Kreeshan et al, 2021, Matsutani et al, 2020, Nettis et al, 2020b, Nettis et al, 2020c, Olesen et al, 2019, Patruno et al, 2021a, Patruno et al, 2021b, Quint et al, 2020, Ribero et al, 2020, Sears et al, 2020, Tauber et al, 2019, Uchida et al, 2021, Uchida et al, 2019. Patruno et al reported the effectiveness and safety of dupilumab in elderly patients with AD in real life (Patruno et al, 2021a, Patruno et al, 2021b.…”
Section: Effectiveness and Safety Of Dupilumab For Atopic Dermatitis In The Real Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Dupilumab, a fully human monoclonal antibody which blocks signaling pathways of interleukin (IL)‐4 and IL‐13, was shown to be effective in treating patients with atopic dermatitis (AD) in daily practice 1 . There have been few studies on drug survival of dupilumab in AD patients in Western countries 2–5 .…”
Section: Figurementioning
confidence: 99%
“…Dupilumab, a fully human monoclonal antibody which blocks signaling pathways of interleukin (IL)-4 and IL-13, was shown to be effective in treating patients with atopic dermatitis (AD) in daily practice. 1 There have been few studies on drug survival of dupilumab in AD patients in Western countries. [2][3][4][5] In this study, we investigated the drug survival rate of Japanese AD patients, reasons for drug discontinuation, and predictive parameters of drug survival.…”
Section: Drug Survival Rate Of Dupilumab In Japanese Patients With Atopic Dermatitismentioning
confidence: 99%